The Early to Middle Eocene Transition: An Integrated Calcareous Nannofossil and Stable Isotope Record From the Northwest Atlantic Ocean (Integrated Ocean Drilling Program Site U1410). Issue 12 (4th December 2019) - Cappelli, C.; Bown, P. R.; Westerhold, T.; Bohaty, S. M.; de Riu, M.; Lobba, V.; Yamamoto, Y.; Agnini, C.
Abstract: The early to middle Eocene is marked by prominent changes in calcareous nannofossil assemblages coinciding both with long‐term climate changes and modification of the North Atlantic deep ocean circulation. In order to assess the impact of Eocene climate change on surface water environmental conditions of the Northwest Atlantic, we developed calcareous nannoplankton assemblage data and bulk stable isotope records (δ 18 O and δ 13 C) across an early to middle Eocene interval (~52–43 Ma) at Integrated Ocean Drilling Program Site U1410 (Southeast Newfoundland Ridge, ~41°N). At this site, early Eocene sediments are pelagic nannofossil chalk, whereas middle Eocene deposits occur as clay‐rich drift sediments reflecting the progressive influence of northern‐sourced deep currents. Between the end of Early Eocene Climatic Optimum (EECO) and the Ypresian/Lutetian boundary, calcareous nannofossils switched from an assemblage mainly composed of warm‐water and oligotrophic taxa ( Zygrhablithus, Discoaster, Sphenolithus, Coccolithus ) to one dominated by the more temperate and eutrophic reticulofenestrids. The most prominent period of accelerated assemblage change occurred during a ~2‐Myr phase of relatively high bulk δ 18 O values possibly related to the post‐EECO cooling. Although the dominance of reticulofenestrids persisted unvaried throughout the middle Eocene interval, early Lutetian (~47.4 to 47 Ma) stable isotope records indicate a reversal in the paleoenvironmetal trends suggesting a potential restoration of warmer conditions. Importantly, our data indicate that the ~2‐Myr interval immediately following the EECO was crucial in establishing the modern calcareous nannofossil assemblage structure and also reveal that the establishment of Reticulofenestra ‐dominated assemblage occurred prior to the onset of persistent deep current system in the Northwest Atlantic. Key Points: Calcareous nannofossil and stable isotope record from Northwest Atlantic Ocean spanning the early to middle Eocene The switch from warm‐oligotrophic to temperate meso‐eutrophic assemblages occurred in the aftermath of the Early Eocene Climatic Optimum Restoration of warmer condition during the early middle Eocene is associated with minor changes in calcareous nannofossil assemblages